2003
DOI: 10.1007/s00404-003-0549-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal peripheral T helper 1-type and T helper 2-type immunity in women during the first trimester of twin pregnancy

Abstract: Our findings show marked predominance of Th2 type cytokines occurring in twin pregnancies is related to the increase in trophoblasts during the first trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…We hypothesize that, in addition to a generalized status of immunological deficiency or insufficiency, the copresence of twins in utero may induce a deeper immune tolerance that involves both fetuses and the mother in order to avoid the potentially harmful immune reaction between the three. Our hypothesis is in accordance with previous studies that documented higher levels of Th2-cytokines in the blood of mothers carrying twins compared with singleton pregnancies [24] underlining the more profound Th1-Th2 shift that occurs in twin pregnancies. Moreover, a recent study demonstrated that both dizygotic twins and their mothers are more prone to infection than monozygotic twins, singletons, and their mothers [25].…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesize that, in addition to a generalized status of immunological deficiency or insufficiency, the copresence of twins in utero may induce a deeper immune tolerance that involves both fetuses and the mother in order to avoid the potentially harmful immune reaction between the three. Our hypothesis is in accordance with previous studies that documented higher levels of Th2-cytokines in the blood of mothers carrying twins compared with singleton pregnancies [24] underlining the more profound Th1-Th2 shift that occurs in twin pregnancies. Moreover, a recent study demonstrated that both dizygotic twins and their mothers are more prone to infection than monozygotic twins, singletons, and their mothers [25].…”
Section: Discussionsupporting
confidence: 93%
“…Normal human pregnancies are distinguished by a Th2 bias (Poole and Claman, 2004;Kidd, 2003;Sacks et al, 2003;Suzuki and Okudaira, 2004;Shimaoka et al, 2000;Lim et al, 2000;Piccinni et al, 2000;Saito et al, 1999). The shift from Th1 cytokine production to Th2 cytokine production protects the semi-allogeneic fetus from rejection by the maternal immune system, but as gestation progresses a shift from a predominate Th2 response to a Th1 response occurs (Raghupathy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…. The median (range) gestational age at sample collection was 22(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) weeks; a2V concentrations were positive correlated with gestational age at sample collection (P = 0.023, Spearman r = 0.237) but not with maternal age. Thirtyseven pregnancies were conceived with no intervention or following intrauterine insemination or ovarian stimulation, and 56 were conceived by in vitro fertilization-embryo transfer.…”
mentioning
confidence: 91%
“…An elevated level of the Th2 subclass of T lymphocytes and a decreased Th1-Th2 T lymphocyte ratio has been observed in mothers with twins compared to those with singleton pregnancies. 17,18 In the present study, we evaluated if a2V levels in peripheral blood mononuclear cells (PBMCs) were different depending on fetal sex, and if this was reflected in associations with birthweight and gestational age at delivery.…”
Section: Introductionmentioning
confidence: 99%